PENERAPAN PEMELAJARAN TERINTEGRASI MODEL TEMATIK UNTUK MEINGKATKAN PEMAHAMAN PANGAN TRADISIONAL DI SEKOLAH DASAR - Marwanti Marwanti (Jurnal Cakrawala Pendidikan, 2006)
Improvements on traditional foods in the society of their origin have been made by processing them in certain ways, giving them particular treatments, and mixing them with specific flavour. Each of such foods has a typical taste and appearance, fits in with some regional condition, and already becomes the daily consumtion of acertain part of society but, as they frow side by side with various foods from other countries, their existence in the present era of flobalization has lately become almost laborius due to such factors as a fhanging lifestyle, economic growth, the intensive promotion of various foreign foods, and the availability of such foods from abroad in the native country of the aforesaid traditional foods.